Laporan Kegiatan Pemberdayaan Masyarakat Mengenai Hipertensi di Lingkungan Cintarasa Kelurahan Kahuripan - Kevin Nicholas; Nazma Izzati Arva E; Nur Azmi Syahla; Rihan Subagja; Margaretha Yessa; Andy Muharry (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Hypertension is one of the non-communicable diseases that poses a global health problem and is a leading cause of death worldwide, including in Indonesia. According to the 2018 Riskesdas data, the prevalence of hypertension in Indonesia reached 34.1%, with most cases occurring in the elderly. Addressing this issue requires a multidisciplinary approach and community empowerment. This study was conducted in RW 01, Kahuripan Village, Tawang District, Tasikmalaya City, aiming to enhance community awareness and skills in managing hypertension through education and the utilization of celery plants.The method used was a participatory descriptive approach. Data were collected through observations, in-depth interviews, and focus group discussions with community leaders and Posyandu cadres. Activities included education about hypertension, distribution of celery plants, and monitoring the community's application of the knowledge gained. Data analysis was conducted qualitatively to evaluate community responses and behavioral changes. The results showed a positive response from the community. Participants actively engaged in the educational sessions, started planting celery at home, and demonstrated increased awareness to regularly check their blood pressure at Posbindu. The education provided successfully improved the community's understanding of hypertension and the benefits of a healthy lifestyle. This study concludes that community-based empowerment is an effective strategy for addressing local health problems sustainably.